HCV viral decline at week 2 of Peg-IFN-alpha-2a/RBV therapy as a predictive tool for tailoring treatment in HIV/HCV genotype 1 co-infected patients. - Antonio Rivero-Juarez (PLoS ONE, 2014)
Optimizing HCV genotype 1 therapy in terms of response prediction and tailoring treatment is undoubtedly the cornerstone of treating HIV co-infected patients in clinical practice. Accordingly, our aim was to analyze the predictive value of HCV viral decline for sustained virological response (SVR), measured at a time point as early as week 2 of therapy with pegylated interferon alpha-2a plus ribavirin (Peg-IFN/RBV).Previously untreated HIV/HCV genotype 1 co-infected patients were included in this study. The HCV RNA titer was measured at week 2 after starting treatment with Peg-IFN/RBV. The likelihood of reaching SVR when HCV RNA viral titers declined at week 2 was evaluated relative to predictive baseline factors.A total of 192 HIV/HCV genotype-1 co-infected patients were enrolled in the study and began therapy. One hundred and sixty-three patients completed a full course of Peg-IFN/RBV treatment for 2 weeks and 59 of these (36.2%) reached SVR. An HCV RNA viral load decline of ≥1.5 log IU/mL at week 2 had the maximum positive predictive value for SVR (83.3%; 95% CI: 68.5%-92.9%) and was identified as the strongest independent predictive factor for reaching SVR across all baseline predictive factors.HCV viral decline at week 2 had a high predictive value for identifying patients with a high and low likelihood of reaching SVR using dual therapy, regardless of strong predictive baseline factors. This finding may be useful for developing a predictive tool to help tailor HCV genotype 1 therapy in HIV co-infected patients.